Role of entrepreneurial passion between entrepreneurial attitude, subjective norms, perceived behavioral control, and entrepreneurial intention: Measuring the entrepreneurial behavior of Pakistani students - Abdul Majeed; Abdul Rasheed Ghumman; Qamar Abbas; Zafar Ahmad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
This study aims to investigate the role of entrepreneurial passion between entrepreneurial attitude, subjective norms, perceived behavioral control, and entrepreneurial intention while measuring the entrepreneurial behavior of Pakistani students. The study has applied the quantitative methods to empirically test the study model and proposed hypotheses using the PLS-SEM technique in the computer version 3.0 of the Smart PLS software. The data were collected from the 240 university students using the structured questionnaire and the sample was drawn randomly. The results have shown significant positive relationship between subjective norms, perceived behavioral control, and entrepreneurial intentions. Similarly, students' entrepreneurial behavior is positively influenced by perceived behavioral control and entrepreneurship intention. In the case of mediation, the entrepreneurial intention significantly and positively intermediates the relationship between subjective norms, perceived behavioral control, and entrepreneurial behavior. Next is the case of moderation, the entrepreneurial passion does not moderate the associations of entrepreneurial attitude, subjective norms, perceived behavioral control, and entrepreneurial intention. These findings contribute to broadening the paradigm of the theory of planned behavior by incorporating entrepreneurial passion and bridging a literature gap between the associations of attitudinal factors, entrepreneurial passion entrepreneurial intention, and entrepreneurial behavior. These findings can be helpful for policy-makers, practitioners, small-medium enterprises to promote entrepreneurship culture in emerging countries, and also helpful for university graduates for creating new business ventures or to become self-employed in order to reduce employment pressure after completing university education.
Keywords: 330; Entrepreneurial attitude; subjective norms; perceived behavioral control; entrepreneurial intention; entrepreneurial behavior; entrepreneurial passion